2021
DOI: 10.3389/fpsyg.2021.696160
|View full text |Cite
|
Sign up to set email alerts
|

To Punish or to Restore: How Children Evaluate Victims' Responses to Immorality

Abstract: Punishment is important for deterring transgressions and maintaining cooperation, while restoration is also an effective way to resolve conflicts and undo harm. Which way do children prefer when evaluating others' reactions to immorality? Across four experiments, Chinese preschoolers (aged 4–6, n = 184) evaluated victims' different reactions to possession violations (i.e., punishing the perpetrator or restoring the belongings). Children evaluated restorative reactions more positively than punitive ones. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
(109 reference statements)
2
6
1
Order By: Relevance
“…These results contrast with earlier findings that infants and children prefer norm enforcers over non-enforcers when the only mode of intervention is punishment or verbal reproach of a transgressor ( Hamlin et al, 2011 , Vaish et al, 2016 ). Instead, the current results are largely in line with more recent findings on children’s judgment in the context of fairness or ownership violations ( Lee and Warneken, 2020 , Liu et al, 2021 ), showing that children’s preference for a helpful over punitive intervention extends to the context of health-related harm (although the prior studies involved a preference for a helpful intervention directed to a victim, not toward a transgressor). Hence, the current study highlights the need to study children’s judgments of interventions other than punishment in various moral contexts.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results contrast with earlier findings that infants and children prefer norm enforcers over non-enforcers when the only mode of intervention is punishment or verbal reproach of a transgressor ( Hamlin et al, 2011 , Vaish et al, 2016 ). Instead, the current results are largely in line with more recent findings on children’s judgment in the context of fairness or ownership violations ( Lee and Warneken, 2020 , Liu et al, 2021 ), showing that children’s preference for a helpful over punitive intervention extends to the context of health-related harm (although the prior studies involved a preference for a helpful intervention directed to a victim, not toward a transgressor). Hence, the current study highlights the need to study children’s judgments of interventions other than punishment in various moral contexts.…”
Section: Discussionsupporting
confidence: 90%
“…Further, we chose giving a new mask to a norm violator as a helpful intervention. To be specific, unlike previous research that identified compensation of a victim as a feasible alternative intervention in a fairness or ownership violation context (e.g., Lee and Warneken, 2020 , Liu et al, 2021 ), we identified that giving a new mask to a person not wearing a mask is a more relevant, helpful reaction in the COVID-19 context than compensating victims (i.e., giving a new mask to a potential victim who is already wearing it). Finally, we included doing nothing (no intervention) to examine if children think that an intervention is even needed in the context.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Thus, we investigate here a range of factors that could potentially modulate children's choices between punishment and compensation, the affective states following the enactment of these two types of third-party interventions, as well as the motivational basis of punishment. Given that most of the literature on children's third-party interventions has been conducted in Northern European and Northern American countries (but see Yang et al, 2021 andLiu et al, 2021), we included children from three different countries (UK, Italy and Colombia) to increase diversity in the sample. Our analysis focuses on commonalities rather than differences across countries.…”
Section: General Introductionmentioning
confidence: 99%